Peningkatan Karakter dan Literasi Akuntansi melalui Media Tabungan Kebaikan sebagai Upaya Pencegahan Bullying - Budiharjo, Roy; Sagita, Ardio; Alfaiza , Salsabila Aisyah (Rahmah : Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to strengthen anti-bullying character while introducing basic accounting literacy through the "Tabungan Kebaikan" (Kindness Savings) medium. The program was conducted on December 12, 2025, at Pondok Pesantren Salafiyah Al Falah, Bojongsoang District, Bandung Regency, involving 40 students. Activities included school coordination, pre-test, delivery of bullying prevention and introductory accounting materials, simulation and role-play practice with daily behavior recorded as "transactions" (positive behavior as deposits/debits; negative behavior including bullying as withdrawals/credits), post-test, and satisfaction evaluation using a Likert scale (1–5). Results demonstrated improved student understanding of basic accounting concepts (debit, credit, balance) and heightened awareness of bullying's impact and the importance of prosocial behavior. Satisfaction evaluations were highly positive, with 86% of respondents agreeing or strongly agreeing on program alignment with objectives, target needs, and implementation quality.